Transcriptome analysis identifies key regulatory genes and temporal expression dynamics during embryonic development in the Japanese eel (Anguilla japonica) - Zhaowei Zhong; Dingyuan Luo; Yizhen Lu; Zebin Chen; Ning Xi; Shengkai Shi; Jincan Chen; Yonghua Jiang (Molecular Genetics and Genomics, 2026)

Potential roles of MyoD in promoting myogenesis and muscle growth in Fenneropenaeus chinensis - Xia Lu; Zebin Zhang; Nan Jiang; Yongzheng Tang; Fangrui Lou; Yan Liu; Tingjin Lü; Xuewei Qu (Journal of Oceanology and Limnology, 2026)

Impact of vortex ecohydraulic complexity on fish collective dynamics and behavioral diversity under varied obstacle geometries - Chenyang Cao; Xiyin Zheng; Shikang Liu; Zebin Zhang; Li Tian; Yike Li; Zhiyuan Yang; Jiabin Lu; Weiwei Yao (Advances in Water Resources, 2026)

Gene cloning and expression analysis based on primary culture of fin cells from Centropyge vrolikii - Dingyuan Luo; Ning Xi; Shengkai Shi; Yizhen Lu; Zebin Chen; Hongwei Liu; Jincan Chen; Hai Huang; Zhaowei Zhong; Yonghua Jiang (Journal of Fish Biology, 2026)
Skin coloration is a distinctive phenotype and an economically important trait in ornamental fish. Understanding its regulatory mechanisms is crucial for both aquaculture and selective breeding. In this study, we cloned and analysed the full‐length complementary DNA (cDNA) sequences of four key pigmentation‐related genes— mitf , mc1r , tyr and sox10 —in the black‐tailed angelfish ( Centropyge vrolikii ). We established the fin‐derived tissue cell line of C. vrolikii (CVFTCL) and confirmed its transfection efficiency using EGFP, achieving 40%–50% expression 24 h post‐transfection, providing an in vitro platform for subsequent gene function verification. Using the primary fin cell culture system, we conducted overexpression and RNA interference (RNAi) experiments to investigate the regulatory relationships among these genes. Overexpression of mitf upregulated mc1r but downregulated sox10 and tyr ; overexpression of mc1r enhanced mitf expression while inhibiting sox10 and tyr ; overexpression of tyr only increased tyrp1 expression and overexpression of sox10 upregulated both mc1r and mitf , without affecting tyr . RNAi‐mediated knockdown confirmed the efficiency of gene silencing and supported the regulatory relationships inferred from overexpression experiments. Collectively, these findings indicate that mitf , mc1r , tyr and sox10 may interact to coregulate melanocyte development and melanin synthesis, thereby influencing skin coloration in C. vrolikii . This study provides a mechanistic framework for pigmentation regulation and a foundation for colour improvement and selective breeding in this species.

Impacts of channel complexity and main-to-anabranch width ratio on fish habitat suitability across varying flow regimes - Pingping Zhou; Hao Zheng; Qianqian Wang; Ruida Wang; Nan Wang; Yongsen Zhang; Yike Li; Zebin Zhang; Li Tian; Zhiyuan Yang; Jiabin Lu; Weiwei Yao (Ecological Engineering, 2026)

Thermal activation in oxidative model drives catechin assembly into theaflavins with enhanced antioxidant capacity - Yuxuan Zhao; Jingyimei Liang; Rui Lu; Zebin Zou; Haoming Wu; Shengxiong Chen; Hui Cao; Jianbo Xiao (Food Chemistry, 2026)

Reactive oxygen species (ROS) potentially affected survival rate after ionizing radiation in scallops - Zebin Zhang; Rui Wang; Jieshan Lin; Zhiqian Gong; Haowen Cao; Chunde Wang; Xia Lu (Fish & Shellfish Immunology, 2026)

The embodied agricultural NH3 emissions in China's inter-provincial trade and the implied environmental inequities - Lu Lu; Zebin Zhao; Jinpan Jiang; Fan Meng; Ziyi Wang; Changshun Wang; Jingchao Li; Hong Qi; Donglei Fu (Journal of Cleaner Production, 2025)

AI models still lag behind traditional numerical models in predicting sudden-turning typhoons - Daosheng Xu; Zebin Lu; Jeremy Cheuk-Hin Leung; Dingchi Zhao; Yi Li; Yang Shi; Bin Chen; Gaozhen Nie; Naigeng Wu; Xiangjun Tian; Yi Yang; Shaoqing Zhang; et al. (Science Bulletin, 2025)

Formation and structural dynamics of Lotus seed starch-linolenic acid complexes under high pressure microfluidization and their evolution during simulated gastrointestinal digestion - Lu Liu; Qi Lin; Yixiang Zhang; Xiaoying Wang; Baodong Zheng; Zebin Guo (Food Chemistry, 2025)

Tree-ring dating of the construction of the Yinshan tomb in Shaoxing, Zhejiang Province: A preliminary study - Shiyuan Shi; Congcong Xiao; Zebin Li; Yongxiang Wang; Hui Wang; Zhansheng Niu; Hongyan Zhang; Pengyu Lin; Xinrui Liu; Lingling Lu; Jiangfeng Shi; Huayu Lu (Science China Earth Sciences, 2025)

Flexible, transparent and conductive silver line electrodes fabricated using surface energy-directed assembly process on polyethylene naphthalate substrates - Yihuan Wang; Siqing Yuan; Guangji Wang; Zebin Fan; Jingwei Zhang; Zetong Li; Chenhua Liu; Dewen Zhao; Zhimin Chai; Xinchun Lu (Chemical Engineering Journal, 2025)

Impact of lotus seed Starch-EGCG complex on gut microbiota: Structural changes and fermentation effects - Ru Jia; Lu Liu; Wenjing Chen; Wenyu Chen; Xiaoying Wang; Zebin Guo (Food Bioscience, 2025)

Marine glycoproteins: a mine of their structures, functions and potential applications - Xiaodan Lu; Luyao Huang; Jiaqi Chen; Yujia Ou; Jingru Wu; David Mahoudjro Bodjrenou; Jiamiao Hu; Yi Zhang; Mohamed A. Farag; Zebin Guo; Jianbo Xiao; Baodong Zheng (Critical Reviews in Food Science and Nutrition, 2024)

Comparative study on dynamic in vitro digestion characteristics of lotus seed starch-EGCG complex prepared by different processing methods - Wenjing Chen; Ru Jia; Lu Liu; Wanyi Lin; Zebin Guo (Food Chemistry, 2024)

Combinatorial Optimization of Physics Parameterization Schemes for Typhoon Simulation Based on a Simple Genetic Algorithm (SGA) - Zebin Lu; Jianjun Xu; Zhiqiang Chen; Jinyi Yang; Jeremy Cheuk-Hin Leung; Daosheng Xu; Banglin Zhang (Journal of Meteorological Research, 2024)

Amyloid fibrils-regulated high-moisture extruded soy proteins: Texture, structure, and taste - Yixin Zheng; Yixin Gao; Cuixia Sun; Yiguo Zhao; Yiping Cao; Wei Lu; Zebin Guo; Yapeng Fang (Food Hydrocolloids, 2023)

Structural characterization and hypoglycemic activity of glycoproteins extracted from Porphyra haitanensis by ammonium sulfate and ethanol extraction methods - Yujia Ou; Yuehong Guo; Lijingting Xu; Xiaodan Lu; Zebin Guo; Baodong Zheng (Food Bioscience, 2023)

Cu doping and Ti3C2OH quantum dots co-modifications of Zn3In2S6 boosted photocatalytic reduction of CO2 to CO via accelerating carriers transfer and enhancing CO2 adsorption and activation - Jinhang Yang; Yanping Hou; Jiangli Sun; Ting Liang; Tingting Zhu; Jiaxiang Liang; Xiaoqiong Lu; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Chemical composition and nutritional function of olive (Olea europaea L.): a review - Zebin Guo; Xiangze Jia; Zhichang Zheng; Xu Lu; Yafeng Zheng; Baodong Zheng; Jianbo Xiao (Phytochemistry Reviews, 2018)

Nutritional composition, physiological functions and processing of lotus (Nelumbo nucifera Gaertn.) seeds: a review - Yi Zhang; Xu Lu; Shaoxiao Zeng; Xuhui Huang; Zebin Guo; Yafeng Zheng; Yuting Tian; Baodong Zheng (Phytochemistry Reviews, 2015)